An investigation of the self-heating phenomenon in viscoelastic materials subjected to cyclic loadings accounting for prestress. (June 2015) - de Lima, A.M.G.; Rade, D.A.; Lacerda, H.B.; Araújo, C.A.
Abstract: It has been demonstrated by many authors that the internal damping mechanism of the viscoelastic materials offers many possibilities for practical engineering applications. However, in traditional procedures of analysis and design of viscoelastic dampers subjected to cyclic loadings, uniform, constant temperature is generally assumed and do not take into account the self-heating phenomenon. Moreover, for viscoelastic materials subjected to dynamic loadings superimposed on static preloads, such as engine mounts, these procedures can lead to poor designs or even severe failures since the energy dissipated within the volume of the material leads to temperature rises. In this paper, a hybrid numerical–experimental investigation of effects of the static preloads on the self-heating phenomenon in viscoelastic dampers subjected to harmonic loadings is reported. After presenting the theoretical foundations, the numerical and experimental results obtained in terms of the temperature evolutions at different points within the volume of the viscoelastic material for various static preloads are compared, and the main features of the methodology are discussed. Highlights: Self-heating analysis of viscoelastic dampers due to the static and dynamic loadings. Numerical and experimental studies of the self-heating in a 3D viscoelastic damper. Curve-fitting procedure to identify the unknown thermal parameters used in the FE model. Validation of the proposed FE modeling procedure of the self-heating by experiments.